Availability and use of Automated External Defibrillators in Karachi, Pakistan: a cross-sectional study - Shoukat Ali, Huma; Seth Martins, Russell; Maha, Quratulain; Syeda Sadia Fatima; Docherty, Charles (Journal of the Pakistan Medical Association, 2022)
Objective: To assess the availability and use of automated external defibrillators in various public and private establishments, and to assess knowledge, attitude and practices related to its use. Methods: The telephone-based survey was conducted from March to August 2019 in Karachi after approval from the ethics review committee of the Aga Khan University, Karachi, and comprised public and private establishments identified through purposive sampling based on the standard requirements for automated external defibrillators installation. Data was collected using a predesigned questionnaire which was pilot-tested for reliability and validity. Data was analysed using SPSS 23. Results: Of the 53 establishments, 32(60.4%) were private and 21(39.6%) were public. Overall, 9(17%) establishments were aware of automated external defibrillators and 1(1.9%) had an automated external defibrillator on the premises. Also, 25(47.2%) establishments believed that having an automated external defibrillator on the premises would be useful, while 25(47.2%) were undecided. Besides, 22(41.5%) establishments said they would consider installing an automated external defibrillator on the premises, while 24(45.3%) were undecided. Finally, 37(69.8%) establishments expressed a positive desire to get trained in giving basic life support. Conclusion: There was a need for a city-wide automated external defibrillator placement project for a reduction in mortality due to out-of-hospital cardiac arrest. Key Words: Defibrillator, Resuscitation, Training, Bystanders.